Design and performance assessment of a hydrographic unmanned surface vessel for enhanced autonomous bathymetry operations in shallow water areas - Norazaruddin, Muhammad Aiman; Zainal Abidin, Zulkifli; Tengku Anuar, Tengku Aizat (National Institute of Science Communication and Policy Research, 2024)
This paper details the development and performance evaluation of an Unmanned Surface Vessel (USV) designed for enhanced autonomous bathymetry in shallow water areas. Through significant technological enhancements, including the integration of a CXSense controller, M1G2 GNSS receiver, KVH C100 magnetic compass, and SBG System INS, the USV demonstrated exceptional operational capabilities. Performance metrics revealed a cross-track error of 0.92 to 2.39 meters, surpassing the International Hydrographic Organization's Category 2 standards. The study outlines the comprehensive upgrades undertaken on the USV’s propulsion, GNSS positioning, course control, and data transmission systems, which collectively facilitated robust automated operations. The successful deployment of low-cost multi-GNSS receivers illustrates a shift toward more economical hydrographic survey methods, challenging the need for expensive professional-grade equipment. The findings underscore the potential of USVs in revolutionising hydrographic surveying, offering substantial improvements in cost-efficiency, operational flexibility, and data accuracy, thereby enhancing marine research and commercial maritime operations